Event-related differences in the cross-sectional areas and torque generation capabilities of quadriceps femoris and hamstrings in male high school athletes - Hoshikawa, Y.; Muramatsu, M.; Iida, T.; Uchiyama, A.; Nakajima, Y.; Kanehisa, H. (Journal of Physiological Anthropology, 2010)
This study investigated the event-related differences in the cross-sectional areas (CSAs) and torque generation capabilities of the quadriceps femoris (QF) and hamstrings (HAM) in male high school athletes. Subjects were soccer players (n=32), volleyball players (21), rowers (29), karate athletes (18), sumo wrestlers (15), sprinters (22), throwers (16), and nonathletes (20). The CSAs of QF and HAM at the mid-thigh were determined using magnetic resonance imaging. In addition, isokinetic torques during knee extension and flexion were determined at a pre-set velocity of 1.05 rad/s. The CSAs of the two muscle groups and torques developed in the two motions were significantly related to the two-third power of lean body mass (LBM2/3) and the product of CSA and femur length (CSA*fl), calculated as an index of muscle volume, respectively. CSA relative to LBM2/3 for QF did not differ among the groups, but that for HAM was higher in sprinters, soccer players, throwers, and karate athletes than in sumo wrestlers, rowers, volleyball players, and nonathletes. Knee extension torque relative to the CSA*fl of QF was higher in karate athletes, soccer players, and rowers than in nonathletes, but the corresponding value for knee flexion did not differ among groups. Thus, the present study indicated that, at least in male high school athletes, the event-related differences in LBM and the muscularity of QF and HAM produced the corresponding differences in the CSAs of the reciprocal muscle groups and knee extension and flexion torques, respectively. However, specific profiles related to competitive and/or training styles exist in HAM CSA and knee extension torque, which cannot be explained by the magnitude of LBM and QF CSA, respectively.